Chondrobot-2: A simple and efficient semi-autonomous tele-robotic lunar excavator - Rhaman, Md. Khalilur; Hossain, Md. Jonayet; Anik, Kazi Mohammad Razin; Oyon, Mahmudul Hasan; Nabia, Sarah Binte Nasir; Rahi, Nabil Shaker; Khan, Bonny Amin; Miran, Md. Mashiur Rahman; Bhuian, Belal Hossain; Rahman, Md. Mosaddequr (© 2012 IEEE, 2017)
This conference paper was presented in the 15th International Conference on Computer and Information Technology, ICCIT 2012; Chittagong; Bangladesh; 22 December 2012 through 24 December 2012 [© 2012 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCITechn.2012.6509787